Intra-abdominal hypertension/abdominal compartment syndrome of pediatric patients in critical care settings - Marjanovic Vesna G.; Budic Ivana Z.; Zecevic Maja D.; Stevic Marija M.; Simic Dusica M. (Open Medicine)
Intra-abdominal hypertension (IAH)/abdominal compartment syndrome (ACS) is one of the rarer clinical entities in the pediatric population, carrying a high degree of morbidity and mortality. The focus of this review is on assessing pathophysiological changes of organ systems in pediatric patients with risk factors for the occurrence of IAH/ACS based on the evaluation of diagnostic modalities and therapeutic strategies.